Invertible secret image sharing scheme based on improved FEMD - Limin MA; Jiahui WANG (Tongxin xuebao)
Based on the improved FEMD algorithm an invertible secret image sharing scheme was proposed.Firstly,the embedding process of secret data was improved to make the original pixel pair and the stego pixel-pair to become a one-to-one mapping.Then a unique status flag was set to be calculated to record and process the original status of the over flow pixel-pair.Experimental data and analysis show that the proposed algorithm can guarantee the generation of high quality cryptographic images and solve the problem that the original carrier image can not be restored.